The specific of economic competitiveness evaluation of cities from cross-border region under the context of urban shrinkage - Jurgita Bruneckiene; Jolita Sinkiene (Institute of Economic Research (IER), 2015)
This article analyzes the issues of economic competitiveness evaluation of cross-border cities under the context of urban shrinkage. Currently the "urban shrinkage" issue is on the top of the political agenda in Europe. Under the globalization conditions, especially cities, which suffer from urban shrinkage, have to find new and modern means and attitudes for increasing urban competitiveness. The absence of methodological tools for the evaluation of economic competitiveness of the cities of cross-border regions is becoming one of the obstacles that impede the real identification of the current situation and predicting perspectives of the cross-border urban development and competitiveness. The purpose of the article - to identify the challenges and factors for improvement of economic competitiveness of the cross-border cities under the context of urban shrinkage and to develop methodological guidelines for the evaluation of cross-border regional economic competitiveness based on the findings of analysis performed on Lithuanian-Polish cross-border cities. The article distinguishes basic characteristics of the shrinking cities and related problems that have a direct impact on the improvement of economic competitiveness of the city. The economic competitiveness evaluation methodology on the cross-border cities is developed and its practical applicability is verified, based on the sample of Lithuanian-Polish cities (Alytus, Marijampole (Lithuania) and Elk, Bialystok (Poland). Panevezys and Siauliai are additionally added to the analysis as industrial cities located near Lithuania - Latvia border). Strategic recommendations on improving the economic competitiveness of Lithuanian-Polish cross-border cities are introduced in the context of urban shrinkage.
Keywords: O11; O18; R11; R58; 330; city; cross-border region; economic competitiveness of cities; shrinking cities